Movement patterns of a U-20 national women`s soccer team during competitive matches: Influence of playing position and performance in the first half - Ramos, G. P.; Nakamura, F. Y.; Pereira, L. A.; Junior, W. B.; Mahseredjian, F.; Wilke, C. F.; Garcia, E. S.; Coimbra, C. C. (International Journal of Sports Medicine, 2017)
The aim of this study was to determine the match locomotor characteristics of a sample of U-20 Brazilian female soccer players. Seven international matches were analyzed during the 2015 U-20 South American Championship, using global positioning technology. During a typical match, fullbacks and forwards covered greater distances in high-intensity running and sprinting than central defenders and midfielders (effect size [ES]=1.42-3.69). In the final 15 min of a game, total and highintensity running distance and player load were ˜ 20 to 35 % (ES=0.41-3.86) lower than in the first 15 min period for midfielders, fullbacks, forwards, and central defenders. Sprinting, and high-intensity running distances, and the frequency of accelerations > 2 m.s - 2 immediately after the most intense 5-min period declined in forwards (ES=1.78-2.67), fullbacks (ES=1.96-5.25), midfielders (ES=1.66-3.77), and central defenders (ES=1.50-4.22). Maintaining `high` levels of activity in the first half resulted in ˜ 19 % reductions in the second half for sprinting distance and frequency of accelerations > 2 m.s - 2 (ES=0.43 and 0.88), while increases in these locomotor activities were observed in situations with `low` levels of activity (ES=0.64 and 1.12, for sprinting and accelerations > 2 m.s - 2, respectively) (within-subject analysis). The data demonstrate that high-intensity efforts are reduced during various phases of international matches and overall activity patterns vary among playing positions. This information could be useful in the development and prescription of sex- and age-specific training regimes.